The Rhinesuchidae and early history of the Stereospondyli (Amphibia: Temnospondyli) at the end of the Palaeozoic. Issue 2 (29th May 2017) - Marsicano, Claudia A; Latimer, Elizabeth; Rubidge, Bruce; Smith, Roger M.H
Abstract: The temnospondyl Rhinesuchidae included more than 20 nominal taxa, many of which were based on poorly preserved and taxonomically indeterminate holotypes. In the present contribution, a comprehensive revision of Rhinesuchidae is presented based on a re-examination of every nominal species. As a result, we recognize eight valid species: Rhinesuchus whaitsi, Uranocentrodon senekalensis, Rhinesuchoides capensis nov. com., Rhinesuchoides tenuiceps, Laccosaurus watsoni, Rhineceps nyasaensis, Australerpeton cosgriffi and Broomistega putterilli . A new comprehensive phylogenetic analysis supports the monophyly of the Rhinesuchidae based on several derived character states mainly related to the unique structure of the otic region in the clade. The new hypothesis supports previous schemes where Rhinesuchidae is positioned as the earliest diverging clade of Stereospondyli. Within Rhinesuchidae, a basal split separates the unique Brazilian gavial-like snouted rhinesuchid A. cosgriffi from the rest of the rhinesuchids, represented by African taxa. The recent recognition of putative rhinesuchids in the Cisuralian of tropical Gondwana attests to the origin of the group in the lower latitudes of western Gondwana. Subsequently, rhinesuchids dispersed and diversified into the temperate areas of Gondwana during later Permian times, thus representing the first early radiation of stereospondyls which by the beginning of the Triassic colonized most fresh-water environments across Pangea.